Proceedings of the 11th International Conference on Human-Computer Interaction With Mobile Devices and Services 2009
DOI: 10.1145/1613858.1613932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-player visualization in a location-based chase-and-catch game

Abstract: In our FoxHunt game, virtual foxes are chased on a playground. Foxes and hunters are rendered on a map displayed on GPS-enabled mobile phones. We collected data from three field tests, totalling 130 participants. Approximately half of the players were provided with positions and scores for the other hunters. In the rest of the games, only the foxes and the players' own avatars were rendered. Providing coplayer information did not have a direct impact on gaming scores. However, it increased the reported fun fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, the results were produced by Amazon's Mechanical Turks and thus provided passive judgements only, so these authors still plan to validate their hypotheses in a real-world scenario. Misund et al (2009) reported that revealing information about locations of other players in a collaborative location-aware chase-and-catch game did not affect the performance in the main task; however, it did make the game more 'fun' to play. Nova et al (2010) found out that automatic mutual location awareness made the coordination process within the tested group less efficient, as opposed to the groups whose members used self-reporting on their whereabouts.…”
Section: Influence Of Location-awarenessmentioning
confidence: 99%
“…However, the results were produced by Amazon's Mechanical Turks and thus provided passive judgements only, so these authors still plan to validate their hypotheses in a real-world scenario. Misund et al (2009) reported that revealing information about locations of other players in a collaborative location-aware chase-and-catch game did not affect the performance in the main task; however, it did make the game more 'fun' to play. Nova et al (2010) found out that automatic mutual location awareness made the coordination process within the tested group less efficient, as opposed to the groups whose members used self-reporting on their whereabouts.…”
Section: Influence Of Location-awarenessmentioning
confidence: 99%